Conductive resin composition
By using bisphenol-type epoxy resin, epoxy resin with high boiling point, conductive particles and epoxy resin curing agent in the conductive resin composition, the problem of exhaust gas generated during heating and curing is solved. Excellent effects of conductivity and adhesion are achieved.
Patent Information
- Application Number
- CN202380049159.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-30
- Filing Date
- 2023-06-29
- Publication Date
- 2025-02-14
AI Technical Summary
The conductive resin composition contains a high volatile compound, which causes exhaust gas to be generated during heating and curing, adhere to nearby components, and leads to poor function of electronic components.
Using a conductive resin composition containing a bisphenol-type epoxy resin, an epoxy resin having a boiling point of 300°C or above, conductive particles and an epoxy resin curing agent, the component ratio and the shape and size of the particles are controlled to suppress the displacement. The production of qi.
The mass reduction amount of the conductive resin composition during heating and curing is effectively reduced, the contamination of other components of the electronic components is reduced, and the conductivity and adhesion of the conductive resin composition is ensured.
Smart Images

Figure BDA0005203299100000321 
Figure BDA0005203299100000331
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive resin composition in which generation of outgassing is suppressed. Background Art
[0002] In the past, conductive resin compositions were used for fixing and grounding electrical / electronic components such as smartphones and electronic mobile devices. In recent years, it is known that conductive resin compositions used in electronic components contain reactive diluents and solvents from the perspective of operability (corresponding to Japanese Patent Publication No. 2020-139020 / International Publication No. 2020 / 175056). Summary of the invention
[0003] However, when a conductive resin composition contains highly volatile compounds, these components volatilize as off-gas (volatile gas) during heat curing and adhere to other nearby members, sometimes causing functional failures in electronic components.
[0004] The present inventors have conducted intensive studies to achieve the above-mentioned object and, as a result, have found a method related to a conductive resin composition that suppresses the generation of outgassing, thereby completing the present invention.
[0005] The gist of the present invention will be described below. One embodiment of the present invention for solving the above-mentioned problems relates to the following conductive resin composition.
[0006] [1] A conductive resin composition comprising the following components (A) to (D):
[0007] (A) ingredient: bisphenol epoxy resin;
[0008] (B) component: an epoxy resin having a boiling point of 300° C. or higher (excluding (A) component);
[0009] (C) component: conductive particles;
[0010] (D) Component: epoxy resin curing agent.
[0011] [2] The conductive resin composition according to [1], wherein the content of the epoxy resin having a boiling point of less than 300° C. and the solvent is 1.00% by mass or less based on the total mass of the composition.
[0012] [3] The conductive resin composition according to [1] or [2], wherein the component (B) is an epoxy resin having a boiling point of 300° C. or higher and containing two or more epoxy groups.
[0013] [4] The conductive resin composition according to any one of [1] to [3], wherein the component (B) is a glycidylamine-type epoxy resin.
[0014] [5] The conductive resin composition according to any one of [1] to [4], wherein the mass ratio of the component (A) to the component (B) (component (A):component (B)) is 99:1 to 60:40.
[0015] [6] The conductive resin composition according to any one of [1] to [5], wherein the component (C) includes plate-like conductive particles as the component (c-1) and conductive particles other than the component (c-1) as the component (c-2).
[0016] [7] The conductive resin composition according to [6], wherein the components (c-1) and (c-2) are silver particles.
[0017] [8] The conductive resin composition according to [6] or [7], wherein the mass ratio of the component (c-1) to the component (c-2) (component (c-1) : component (c-2)) is 20:80 to 70:30.
[0018] [9] The conductive resin composition according to any one of [1] to [8], wherein the component (D) is a latent epoxy resin curing agent.
[0019]
[10] The conductive resin composition according to any one of [1] to [9], wherein the component (D) is a modified aliphatic polyamine-based latent epoxy resin curing agent.
[0020]
[11] The conductive resin composition according to any one of [1] to
[10] , wherein the mass loss of the uncured conductive resin composition when the temperature is increased from 25°C to 80°C at a temperature increase rate of 10°C / min and then heated at 80°C for 1 hour is less than 0.2% by mass.
[0021]
[12] A cured product obtained by curing the conductive resin composition according to any one of [1] to
[11] .
[0022]
[13] A conductive resin composition comprising the following components (B) to (D):
[0023] (B) component: a glycidylamine type epoxy resin having a boiling point of 300° C. or higher;
[0024] (C) component: conductive particles;
[0025] (D) Component: epoxy resin curing agent. DETAILED DESCRIPTION
[0026] Next, the details of the present invention will be described. It should be noted that the present invention is not limited to the following embodiments, and various changes can be made within the scope of the technical solution. In addition, the embodiments described in this specification can be combined arbitrarily to form other embodiments.
[0027] Throughout this specification, as far as the expression in singular form is concerned, unless otherwise specified, it should be understood that the expression in singular form also includes the concept of its plural form. Therefore, unless otherwise specified, it should be understood that the article in singular form (for example, "a", "an", "the", etc. in English) also includes the concept of its plural form. In addition, for the terms used in this specification, unless otherwise specified, it should be understood that they are used with the meaning commonly used in the field. Therefore, unless otherwise defined, all professional terms and scientific terms used in this specification have the same meaning as those commonly understood by those skilled in the art in the field to which the invention belongs. In the event of a conflict, this specification (including definitions) takes precedence.
[0028] It should be noted that, in this specification, "X to Y" is used to include the numerical values (X and Y) recorded before and after as the lower limit and upper limit, and means "above X and below Y". In addition, in this specification, the term "(meth)acrylic acid" refers to both acrylic acid and methacrylic acid. In addition, unless otherwise specified, the concentration and % represent the mass concentration and mass %, respectively, and the ratio is set as the mass ratio unless otherwise specified. In addition, unless otherwise specified, the operation and measurement of physical properties are carried out under the conditions of room temperature (20°C to 25°C) / relative humidity 40%RH to 55%RH. In addition, "A and / or B" refers to including A, B individually and their combinations.
[0029] [Conductive resin composition]
[0030] The conductive resin composition according to one embodiment of the present invention (hereinafter, also simply referred to as "the conductive resin composition according to the present invention" or "the conductive resin composition") comprises the following components (A) to (D):
[0031] (A) ingredient: bisphenol epoxy resin;
[0032] (B) component: an epoxy resin having a boiling point of 300° C. or higher (excluding (A) component);
[0033] (C) component: conductive particles;
[0034] (D) Component: epoxy resin curing agent.
[0035] That is, the conductive resin composition of the present invention comprises the above-mentioned (A) to (D) components. By having such a composition, the conductive resin composition of the present invention generates less outgassing. Therefore, it is suitable as a conductive resin composition for bonding electronic components. In addition, for the conductive resin composition of the present invention, both the conductivity and adhesion of its cured product are excellent. The details of its mechanism are not yet clear, but it can be considered that the combination of resins included as the (A) component and the (B) component of the present invention can suppress the generation of outgassing, and the (C) component can improve the conductivity and adhesion of the cured product in a well-balanced manner.
[0036] [(A) ingredient]
[0037] The component (A) used in the present invention is a bisphenol epoxy resin. The conductivity is excellent because the component (A) is a bisphenol epoxy resin. The structure of the component (A) is not limited, but by making the boiling point above 300°C, there is no worry about contaminating electronic components due to the generation of exhaust gas, so a bisphenol epoxy resin with a boiling point of 300°C or above is preferred. The boiling point of the bisphenol epoxy resin of the component (A) is preferably above 300°C, more preferably above 350°C, further preferably above 400°C, particularly preferably above 420°C, and most preferably above 450°C. The component (A) may be solid or liquid, and although not particularly limited, it is preferably a compound having two or more epoxy groups (bisphenol multifunctional epoxy resin) from the aspect of excellent curability, and is preferably liquid at 25°C from the aspect of excellent operability. That is, in one embodiment, as the component (A), it is preferred to have two or more epoxy groups, and more preferably a bisphenol epoxy resin that is liquid at 25°C.
[0038] For bisphenol type multifunctional epoxy resin, the upper limit of the number of epoxy groups contained in one molecule is not particularly limited, and is preferably 6 or less. As an example, the number of epoxy groups contained in the compound as component (A) is preferably 2 to 6 (2 to 6 functional epoxy resins), more preferably 2 to 3 (2 to 3 functional epoxy resins), and particularly preferably 2 (2 functional epoxy resins). It should be noted that the epoxy group may be contained in the compound (epoxy resin) in the form of a glycidyl group.
[0039] Here, in this specification, "liquid" means a state having fluidity at 25°C (liquid state). Specifically, "liquid at 25°C" means that the viscosity of the liquid is 10 s at 25°C using a cone-plate rotational viscometer. -1 The viscosity measured was 1000 Pa·s or less. It should be noted that in this specification, the viscosity of the components is measured using a cone-plate type rotational viscometer at a shear rate of 10 s -1As an example, the viscosity of the multifunctional epoxy resin used as the component (A) at 25°C is preferably 0.01 Pa·s or more and less than 1000 Pa·s, more preferably 0.1 to 500 Pa·s, further preferably 0.3 to 100 Pa·s, particularly preferably 0.5 to 10 Pa·s, and most preferably 0.8 to 5 Pa·s.
[0040] Specific examples of the component (A) include bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S type, bisphenol AD type epoxy resin, urethane modified bisphenol epoxy resin, rubber modified bisphenol epoxy resin, polyoxyalkylene modified bisphenol epoxy resin, etc. These may be used alone or in combination of two or more, and preferably in combination of bisphenol A epoxy resin and bisphenol F epoxy resin from the viewpoint of excellent conductivity and operability.
[0041] When bisphenol A epoxy resin and bisphenol F epoxy resin are used together in component (A), the mass ratio (bisphenol A epoxy resin: bisphenol F epoxy resin) is preferably 90:10 to 10:90, more preferably 85:15 to 15:85, further preferably 80:20 to 20:80, particularly preferably 75:25 to 25:75, and most preferably 70:30 to 30:70, from the viewpoint of excellent curability and workability.
[0042] The epoxy equivalent of the bisphenol epoxy resin used as the component (A) is not particularly limited. From the viewpoint of further improving the adhesive force, it is preferably 50 g / eq or more and 300 g / eq or less, more preferably 100 g / eq or more and 250 g / eq or less, and particularly preferably 130 g / eq or more and 200 g / eq or less. It should be noted that in this specification, the epoxy equivalent is a value measured in accordance with JIS K-7236:2001. In addition, when the epoxy equivalent cannot be obtained by this method, it can also be calculated in the form of a value obtained by dividing the molecular weight of the target epoxy resin (compound) by the number of epoxy groups contained in one molecule of the epoxy resin (compound).
[0043] Commercially available products of component (A) are not particularly limited, and examples thereof include jER828, 1001, 801N, 807 (manufactured by Mitsubishi Chemical Corporation), EPICLON830, 835, 840, 840-S, 850, 850-S, 850-LC, EXA-830CRP, EXA-830LVP, EXA-850CRP, EXA-835LV (manufactured by DIC Corporation), ADEKA RESINEP4100, EP4901, EP4000 (manufactured by ADEKA CORPORATION), DER331, 332, 354, 542 (manufactured by The Dow Chemical Campany), etc. These may be used alone or in combination of two or more.
[0044] [(B) ingredient]
[0045] The component (B) used in the present invention is an epoxy resin having a boiling point of 300°C or more other than the component (A). That is, the component (B) is an epoxy resin having a boiling point of 300°C or more other than the bisphenol epoxy resin. As the component (B), the structure is not limited as long as the boiling point is above 300°C, but by making the boiling point above 300°C, there is no need to worry about contamination of electronic components due to the generation of exhaust. The boiling point of the epoxy resin of the component (B) is preferably above 320°C, more preferably above 350°C, further preferably above 380°C, particularly preferably above 400°C, and most preferably above 410°C. In addition, from the perspective of excellent operability, it is preferably liquid at 25°C. As an example, the viscosity of the epoxy resin used as component (B) at 25°C is preferably 0.01 Pa·s or more and less than 1000 Pa·s, more preferably 0.1 to 500 Pa·s, further preferably 0.3 to 100 Pa·s, particularly preferably 0.4 to 10 Pa·s, and most preferably 0.5 to 5 Pa·s.
[0046] The epoxy resin having a boiling point of 300°C or more as component (B) preferably includes a compound having two or more epoxy groups, more preferably includes a compound having three or more epoxy groups, and most preferably includes a compound having three epoxy groups, from the perspective of excellent curability. According to one embodiment, as component (B), from the perspective of excellent curability, the epoxy group is preferably a group selected from glycidylamino or glycidyloxy. Thus, according to one embodiment, as component (B), it is preferably: an epoxy resin (excluding component (A)) having one or more (preferably two or more) groups selected from glycidylamino and glycidyloxy and a boiling point of 300°C or more.
[0047] Specific examples of the component (B) include alkylene glycol epoxy resins, phenol novolac epoxy resins or cresol novolac epoxy resins, novolac epoxy resins such as biphenyl epoxy resins, hydrogenated bisphenol A epoxy resins, hydrogenated bisphenol F epoxy resins, glycidylamine epoxy resins, naphthalene epoxy resins, urethane-modified epoxy resins, silicone-modified epoxy resins, rubber-modified epoxy resins, rubber-modified epoxy resins, etc. These may be used alone or in combination of two or more, and glycidylamine epoxy resins are preferred from the perspective of excellent curability.
[0048] Examples of the glycidylamine epoxy resin include N,N-diglycidyl-4-glycidyloxyaniline, 4,4'-methylenebis(N,N-diglycidylaniline), tetraglycidyldiaminodiphenylmethane, tetraglycidyl-m-xylylenediamine, 4-(2,3-epoxypropane-1-yloxy)-N,N-bis(2,3-epoxypropane-1-yl)-2-methylaniline, etc. These may be used alone or in combination of two or more.
[0049] The epoxy equivalent of the epoxy resin having a boiling point of 300° C. or higher used as the component (B) is not particularly limited, but is preferably 30 g / eq or more and 200 g / eq or less, more preferably 50 g / eq or more and 180 g / eq or less, and particularly preferably 60 g / eq or more and 150 g / eq or less from the viewpoint of further improving the adhesive force. The epoxy equivalent is a value measured by the above method.
[0050] There are no particular limitations on commercially available products of the component (B), and examples thereof include jER604, jER630, YX4000, YX8000, and YX8034 (manufactured by Mitsubishi Chemical Corporation), ADEKARESIN EP-3950S and EP-3950L (manufactured by ADEKA CORPORATION), Sumi-Epoxy ELM-100, ELM-100H, ELM-434, ELM-434L, and ELM-434VL (manufactured by Sumitomo Chemical Co., Ltd.), YH-404 and YH-513 (manufactured by Nippon Steel Chemicals Co., Ltd.), and Denacol EX252 (manufactured by Nagase ChemteX Corporation).
[0051] The mass ratio of component (A) to component (B) (mass of component (A) : mass of component (B)) is preferably 99:1 to 60:40, more preferably 98:2 to 65:35, further preferably 95:5 to 70:30, and most preferably 95:5 to 75:25, from the viewpoint of obtaining a conductive resin composition having excellent conductivity.
[0052] [(C) ingredient]
[0053] The (C) component used in the present invention is conductive particles. As (C) component, as long as conductivity is shown, the material of the particles is not limited, for example, it can be selected from metal particles composed of one or more metals selected from gold, silver, copper, nickel, palladium, platinum, tin, bismuth, etc., or alloy particles formed by combining them in a variety of ways, or particles formed by coating the surface with the above metal as a coating layer (particles obtained by coating the surface with inorganic filler materials and organic polymers as cores) etc. They can be used alone, or two or more can be used in combination, and from the aspects of conductivity, cost, etc., it is preferred that silver particles and / or silver are used as a coating layer to coat the surface.
[0054] From the viewpoint of excellent conductivity, the average particle size (D50) of the component (C) is preferably in the range of 0.1 to 30 μm, more preferably in the range of 0.5 to 10 μm, and most preferably in the range of 1.5 to 5 μm. Here, the average particle size of the component (C) is the particle size (D50) at a cumulative volume ratio of 50% in the particle size distribution obtained by a laser diffraction scattering method. As an example, the average particle size of the component (C) can be measured by a laser diffraction scattering shape distribution measuring instrument.
[0055] The content of the component (C) is preferably 50 to 500 parts by mass, more preferably 100 to 450 parts by mass, further preferably 150 to 400 parts by mass, particularly preferably 180 to 350 parts by mass, and most preferably 200 to 300 parts by mass relative to 100 parts by mass of the total of the components (A) and (B). When the content of the component (C) is 50 parts by mass or more, excellent conductivity is achieved, and when it is 500 parts by mass or less, a conductive resin composition having excellent workability can be obtained.
[0056] The shape of the component (C) includes spherical, plate-like, flake-like, amorphous, scaly, needle-like, and dendritic shapes, and may be crystalline or amorphous. The component (C) may be used alone or in combination of a plurality of shapes.
[0057] In one embodiment, the (C) component may be plate-like conductive particles (component (c-1)) having a plate-like shape, or may be conductive particles (component (c-2)) having a non-plate-like shape. Therefore, in one embodiment, the (C) component includes one or more selected from the group consisting of component (c-1): plate-like conductive particles and component (c-2): conductive particles other than component (c-1) (not including conductive particles of component (c-1)). Here, component (c-1) and component (c-2) may be used in one kind each, or in combination of two or more kinds.
[0058] In one embodiment, the component (C) preferably includes plate-shaped conductive particles as the component (c-1) and conductive particles other than the component (c-1) as the component (c-2) (excluding the conductive particles of the component (c-1)). By including the conductive particles in combination, a conductive resin composition having excellent conductivity can be obtained.
[0059] The plate-like conductive particles refer to plate-like particles with uniform thickness obtained by growing a metal crystal surface in a large scale, and are generally micrometer-sized (flat surface dimensions) and nanometer-sized in thickness, and have polygonal plate shapes such as triangular plate, hexagonal plate, truncated triangular plate, quadrilateral plate, pentagonal plate, and hexagonal plate. As plate-like conductive particles, preferably, they are plate-like thin flake particles with substantially (roughly or completely) uniform thickness and smooth surfaces.
[0060] The plate-like conductive particles can be produced by a known production method. The production method of the plate-like conductive particles is not particularly limited. As a production method of the plate-like conductive particles, for example, the production method shown in Japanese Patent Application Laid-Open No. 2014-196527 (corresponding to U.S. Patent No. 2016 / 0001362) can be cited.
[0061] The shape and surface state of the particles can be confirmed by general methods such as scanning electron microscope (SEM). When observing the particles using a scanning electron microscope (SEM), in the SEM image, it is visually confirmed that the particles have a plate-like shape, and the distance between the upper and lower surfaces (2 bottom surfaces) of the plate-like shape, that is, the thickness, is substantially (roughly or completely) uniform in one particle, and the bottom surface of the plate-like shape is substantially (roughly or completely) smooth, and the particles can be judged to be plate-type particles. For plate-type particles, when visually confirming the SEM image, the upper and lower surfaces (2 bottom surfaces) of the plate-like shape are substantially (roughly or completely) parallel. It should be noted that in this specification, the plate-like shape does not include a plate-like (curved plate-like) shape with a significantly curved bottom surface. Therefore, in this specification, the plate-like conductive particles do not include curved plate-like conductive particles.
[0062] The deviation of the thickness of the plate-like conductive particles is not particularly limited. In one embodiment, the deviation of the thickness of the plate-like conductive particles is preferably within the range of ±10% relative to the thickness of the powder (plate-like conductive particles), and more preferably within the range of ±5%. It should be noted that the deviation of the thickness of the plate-like conductive particles is determined by measuring the thickness of 3 points of one plate-like silver particle (one particle) using a scanning electron microscope (SEM) and calculating the average value.
[0063] The arithmetic mean roughness Ra of the surface of the plate-like conductive particles is not particularly limited. In one embodiment, the arithmetic mean roughness Ra of the surface of the plate-like conductive particles is preferably less than 10.0 nm, more preferably less than 8.0 nm, and further preferably less than 3.5 nm (lower limit 0 nm). The arithmetic mean roughness Ra of the surface of the plate-like conductive particles is preferably greater than 1.0 nm. As preferred examples of the range of the arithmetic mean roughness of the surface of the plate-like conductive particles, there can be cited 1.0 nm or more and 10.0 nm or less, 1.0 nm or more and 8.0 nm or less, 1.0 nm or more and 3.5 nm or less, but not limited to these. In this specification, the arithmetic mean roughness Ra of the surface of the plate-like conductive particles can be evaluated using an atomic force microscope (AFM). As an example of a method for measuring the arithmetic mean roughness Ra of the surface of (c-1), the method described in paragraphs "0023" to "0025" of Japanese Patent Application Laid-Open No. 2014-196527 (corresponding to U.S. Patent No. 2016 / 0001362) can be cited. More specifically, as an example of a method for measuring the arithmetic mean roughness Ra of the surface of the plate-like conductive particles, the following method can be cited: using a scanning probe microscope SPM-9600 manufactured by Shimadzu Corporation, for example, under the following measurement conditions, the arithmetic mean roughness at a measurement distance of 2 μm in the flattest surface is measured for 10 randomly selected particles (when it is difficult to measure at a distance of 2 μm in the flattest surface, the measurement is performed at a distance as large as possible in the plane), and the average value of the 10 arithmetic mean roughnesses is calculated, and the calculated value is used as the arithmetic mean roughness Ra of the surface of the plate-like conductive particles.
[0064] 《Measurement conditions》
[0065] Mode: Contact mode
[0066] Cantilever: OMCL-TR800 PSA-1 from Olympus Corporation
[0067] Resolution: 512×512 pixels
[0068] Height resolution: 0.01nm
[0069] Lateral resolution: 0.2nm.
[0070] The plate-like conductive particles are preferably particles obtained by growing a metal crystal surface in a large amount. That is, the plate-like conductive particles are preferably single crystals. Single crystals refer to crystals in which the arrangement directions of single atoms or molecules are the same and arranged regularly. By being single crystals, it is possible to obtain a conductive resin composition having excellent conductivity of the cured product such as connection resistance value and volume resistivity. The plate-like conductive particles preferably include single crystal plate-like conductive particles, more preferably single crystal plate-like conductive particles, and further preferably single crystal plate-like silver particles.
[0071] Whether the conductive particles are crystalline can be determined by analyzing the presence or absence of a crystal structure using an X-ray diffraction method (XRD) or an electron diffraction method. For example, in an electron beam diffraction pattern, a situation where a clear diffraction point is obtained is determined to be a crystalline structure, and a situation where a ring-shaped continuous diffraction pattern is obtained instead of a clear diffraction point is determined to be an amorphous structure.
[0072] As long as the plate-like conductive particles as the component (c-1) show conductivity, the material of the particles is not limited, and for example, it can be further appropriately selected from metal particles composed of one or more metals selected from gold, silver, copper, nickel, palladium, platinum, tin, bismuth, etc., or alloy particles composed of a plurality of combinations thereof, or particles formed by coating the surface with the above metals as a coating layer (particles obtained by using an inorganic filler material or an organic polymer as a core and the surface being coated with a metal), etc. They can be used alone or in combination of two or more, but from the perspective of conductivity, cost, etc., it is preferably a particle formed by coating the surface with silver particles and / or silver as a coating layer.
[0073] (c-1) component can be surface treated with a lubricant. The plate-like conductive particles preferably include plate-like conductive particles surface treated with a lubricant, more preferably plate-like conductive particles surface treated with a lubricant, and further preferably plate-like silver particles. As a lubricant, saturated fatty acids or / and unsaturated fatty acids can be used. As a lubricant, for example, capric acid, undecanoic acid, lauric acid, tridecanoic acid, myristic acid, pentadecanoic acid, palmitic acid, heptadecanoic acid, stearic acid, linolenic acid, linoleic acid, palmitoleic acid, oleic acid, etc. can be cited. From the perspective of excellent dispersibility and storage stability, stearic acid is preferred. They can be used alone, or two or more can be used in combination. The lubricant preferably includes at least one selected from the group consisting of the above-mentioned compounds, more preferably at least one selected from the group consisting of the above-mentioned compounds. As an example, the lubricant preferably includes stearic acid, more preferably stearic acid.
[0074] The plate-like conductive particles as the component (c-1) are produced by a known production method, and an example thereof is the production method disclosed in Japanese Patent Application Laid-Open No. 2014-196527.
[0075] Furthermore, the component (c-1) is preferably a single crystal. A single crystal refers to a crystal in which single atoms or molecules are arranged in the same direction and regularly. By using a single crystal, a conductive resin composition having excellent conductivity can be obtained.
[0076] From the viewpoint of excellent conductivity, the average particle size of the plate-like conductive particles as the (c-1) component is preferably 0.1 μm or more and less than 1000 μm. In addition, the average particle size of the plate-like conductive particles is preferably in the range of 0.1 to 30 μm, more preferably in the range of 0.1 to 20 μm, further preferably in the range of 0.2 to 18 μm, particularly preferably in the range of 0.2 to 15 μm, and most preferably in the range of 0.3 to 15 μm. In one embodiment, the average particle size of the (c-1) component can be 0.2 to 10 μm, 0.2 to 8 μm, 0.3 to 10 μm, 0.3 to 5 μm, 0.4 to 15 μm, 0.4 to 10 μm, 0.4 to 5 μm. Here, the average particle size of the (c-1) component is the particle size (D50) at a cumulative volume ratio of 50% in the particle size distribution obtained by a laser diffraction scattering method. As an example, the average particle size of the (c-1) component can be measured by a laser diffraction scattering shape distribution measuring instrument. In addition, although the reason is not yet clear, from the aspect of excellent adhesive force, it is preferred to use two or more kinds of different particle sizes in combination. When two or more kinds of different particle sizes are used in combination, the mass ratio of the large particle size (c-1) component to the small particle size (mass ratio of the large particle size (c-1) component: the small particle size (c-1) component) is preferably 90:10 to 30:70, more preferably 80:20 to 40:60, and most preferably 70:30 to 50:50.
[0077] The thickness (average thickness T) of the plate-like conductive particles as the (c-1) component is not particularly limited. From the viewpoint of excellent conductivity, it is preferably 1 nm or more and less than 1000 nm, more preferably 10 to 200 nm, further preferably 30 to 150 nm, particularly preferably 40 to 120 nm, and most preferably 50 to 100 nm. In one embodiment, the thickness (average thickness T) of the (c-1) component can be 1 to 200 nm, 5 to 150 nm, 10 to 100 nm, 20 to 180 nm, 30 to 150 nm, 40 to 130 nm, 45 to 120 nm, 50 to 110 nm, 60 to 100 nm. The thickness (average thickness T) of the (c-1) component can be confirmed using a scanning electron microscope (SEM). In more detail, 100 plate-like conductive particles are randomly selected, the thickness of each is measured, and the average value is obtained. The thickness of each plate-like conductive particle is measured based on the SEM image.
[0078] The aspect ratio of the plate-like conductive particles as the component (c-1) is not particularly limited. From the viewpoint of excellent conductivity, it is preferably 1.5 or more, more preferably 1.5 to 100, further preferably 5 to 100, particularly preferably 10 to 75, and most preferably 10 to 60. The aspect ratio of the component (c-1) may be 5 to 80 or 8 to 60. In addition, although the reason is not yet clear, from the perspective of excellent adhesive force, it is preferred to use two or more particles with different aspect ratios in combination. When two or more particles with different aspect ratios are used in combination, the aspect ratio of the particles with a large aspect ratio is preferably within the above-mentioned aspect ratio range. When two or more particles with different aspect ratios are used in combination, the aspect ratio of the particles with a small aspect ratio is preferably 1.2 or more, more preferably 1.2 to 50, further preferably 1.3 to 40, particularly preferably 1.4 to 30, and most preferably 1.5 to 20. The mass ratio of the component (c-1) of particles with a large aspect ratio to the component (c-1) of particles with a small aspect ratio (mass ratio of the component (c-1) of particles with a large aspect ratio: the component (c-1) of particles with a small aspect ratio) is preferably 90:10 to 30:70, more preferably 80:20 to 40:60, and most preferably 70:30 to 50:50. The aspect ratio of the component (c-1) can be calculated by calculating (average particle size) / (average thickness T) from the average particle size obtained using a laser diffraction scattering shape distribution measuring instrument and the thickness (average thickness T) confirmed using a scanning electron microscope (SEM).
[0079] The specific surface area of the plate-like conductive particles as the component (c-1) is preferably 0.1 to 7.0 m 2 / g, more preferably 0.3 to 5.0 m 2 / g, more preferably 0.5 to 3.0 m 2 / g, particularly preferably 0.50 to 3.00 m 2 / g, and most preferably 1.00 to 3.00 m 2 / g. If the specific surface area of the plate-like conductive particles is 0.1 m 2 / g or more, a conductive resin composition having excellent conductivity can be obtained. 2 In another embodiment, the specific surface area of the plate-like conductive particles is preferably 0.50 m 2 / g or more, more preferably 0.50 to 7.00 m 2 / g, more preferably 0.50 to 5.00 m 2 / g, particularly preferably 0.50 to 3.00 m 2 / g, and most preferably 0.90 to 3.00 m 2 Here, the specific surface area is a value calculated by the BET method.
[0080] As the plate-like conductive particles of the component (c-1), synthetic products and / or commercial products can be used. The commercial products of the plate-like conductive particles are not particularly limited. The commercial products of the component (c-1) are not particularly limited, and examples thereof include N300, M612, M13, M27, LM1 (manufactured by TOKUSEN KOGYO Co., Ltd.), etc.
[0081] As the plate-like conductive particles of the component (c-1), one type of plate-like conductive particles may be used, or two or more types of plate-like conductive particles may be used in combination.
[0082] The content of the plate-like conductive particles as the component (c-1) is preferably 20 to 300 parts by mass, more preferably 30 to 200 parts by mass, more preferably 35 to 190 parts by mass, particularly preferably 40 to 180 parts by mass, and most preferably 50 to 150 parts by mass relative to 100 parts by mass of the total of the components (A) and (B). According to one embodiment, the content of the component (c-1) may be 30 to 150 parts by mass, 50 to 130 parts by mass, 50 to 120 parts by mass, or 50 to 100 parts by mass relative to 100 parts by mass of the total of the components (A) and (B). By having a content of 20 parts by mass or more of the component (c-1), a conductive resin composition having excellent conductivity and adhesive force can be obtained, and by having a content of 300 parts by mass or less of the component (c-1), a conductive resin composition having excellent operability can be obtained. It should be noted that when two or more bisphenol epoxy resins are used as the component (A), the content of the component (A) refers to their total amount. When two or more epoxy resins having a boiling point of 300 or more are used as component (B), the content of component (B) refers to their total amount. In addition, when two or more plate-like conductive particles are used as component (c-1), the content of component (c-1) refers to their total amount.
[0083] The component (c-2) is conductive particles other than the component (c-1). That is, the component (c-2) is conductive particles other than plate-shaped conductive particles (hereinafter also referred to as "conductive particles of the component (c-2)"), and is conductive particles not included in the component (c-1). The conductive particles of the component (c-2) are not particularly limited in material and shape as long as they are particles that exhibit conductivity. The conductive particles of the component (c-2) can further improve conductivity by combining with the component (c-1).
[0084] The conductive particles of the component (c-2) can be appropriately selected from, for example, metal particles consisting of one selected from gold, silver, copper, nickel, palladium, platinum, tin, bismuth, etc.; alloy particles formed by combining multiple selected from these metals; particles formed by coating the surface with the above metal as a coating layer (particles obtained by using inorganic fillers or organic polymers as cores and the surface being coated with metals), etc. They can be used alone, or two or more kinds can be used in combination. From the perspective of conductivity, cost, etc., (c-2) preferably contains metal particles, more preferably contains metal particles containing at least one selected from gold, silver, copper, nickel, palladium, platinum, tin and bismuth, and further preferably contains silver particles. As an example, from the perspective of conductivity, cost, etc., (c-2) is preferably a metal particle, more preferably a metal particle containing at least one selected from gold, silver, copper, nickel, palladium, platinum, tin and bismuth, and further preferably a silver particle and / or a particle formed by coating the surface with silver as a coating layer.
[0085] The shape of the (c-2) component is not particularly limited. As the shape of the (c-2) component, spherical, amorphous, flaky (scaly), filamentous (needle-shaped) and dendritic shapes can be cited, and they are preferably non-crystalline, preferably flaky. They can be used alone or in combination. Here, in this specification, flaky particles refer to flaky particles other than plate-like particles (flaky particles other than plate-like particles). The (c-2) component preferably contains flaky particles, more preferably contains flaky silver particles, and further preferably flaky silver particles. However, when the (c-2) component contains silver particles, the silver particles are not plate-like silver particles. In addition, regardless of whether the (c-2) component is a silver particle, the (c-2) component is preferably a conductive particle of a shape other than plate-like particles.
[0086] As described above, the shape and surface state of the particles can be confirmed by general methods such as scanning electron microscopy (SEM). Similar to the determination of the shape of the above-mentioned (c-1) component, whether the (c-2) component is a plate-like (plate-like) thin-plate particle with uniform thickness can be determined by observing the particles using a scanning electron microscope (SEM). Similar to the determination of the surface state of the above-mentioned (c-1) component, whether the surface of the (c-2) component is smooth can be determined by observing the particles using an SEM image.
[0087] The deviation of the thickness of the (c-2) component is not particularly limited. When the (c-2) component contains flaky conductive particles, the deviation of the thickness of the flaky conductive particles is preferably greater than ±10% relative to the thickness of its powder (the flaky conductive particles). In another embodiment, it is preferred that the (c-2) component is a flaky conductive particle, and the deviation of the thickness of the flaky conductive particles is greater than ±10% relative to the thickness of its powder (the flaky conductive particles). In another embodiment, the deviation of the thickness of the (c-2) component relative to the thickness of its powder (conductive particles other than plate-like conductive particles) is greater than ±10%, etc. It should be noted that the deviation of the thickness of the (c-2) component is determined by measuring the thickness of 3 points for each (1 particle) of the powder (conductive particles other than plate-like conductive particles) using a scanning electron microscope (SEM) and calculating the average value.
[0088] In one embodiment, as a preferred example, the following examples can be cited: the deviation of the thickness of the (c-1) component is within the range of ±10% (preferably within the range of ±5%, etc.) relative to the thickness of its powder (plate-like conductive particles); when the (c-2) component contains flaky conductive particles, the deviation of the thickness of the flaky conductive particles exceeds ±10% relative to the thickness of its powder (the flaky conductive particles).
[0089] In another embodiment, as a preferred example, the following examples can be cited: the deviation of the thickness of the component (c-1) is within the range of ±10% (preferably within the range of ±5%, etc.) relative to the thickness of its powder (plate-like conductive particles), and the component (c-2) is flaky conductive particles, and the deviation of the thickness of the flaky conductive particles exceeds ±10% relative to the thickness of its powder (the flaky conductive particles).
[0090] In another embodiment, as a preferred example, the following examples can be cited: the deviation of the thickness of the component (c-1) is within the range of ±10% (preferably within the range of ±5%, etc.) relative to the thickness of its powder (plate-like conductive particles), and the deviation of the thickness of the component (c-2) is greater than ±10% relative to the thickness of its powder (conductive particles other than plate-like conductive particles).
[0091] The arithmetic average roughness Ra of the surface of the (c-2) component is not particularly limited. In one embodiment, when the (c-2) component contains flaky conductive particles, the arithmetic average roughness of the surface of the flaky conductive particles is preferably greater than 10.0 nm. When the (c-2) component contains flaky conductive particles, the arithmetic average roughness of the surface of the flaky conductive particles is preferably less than 20 μm. In another embodiment, the (c-2) component is more preferably a flaky conductive particle having an arithmetic average roughness of more than 10.0 nm on the surface. The (c-2) component is preferably a flaky conductive particle having an arithmetic average roughness of less than 20 μm on the surface. In another embodiment, the arithmetic average roughness of the surface of the (c-2) component is more preferably greater than 10.0 nm. The arithmetic average roughness of the surface of the (c-2) component is preferably less than 20 μm. The arithmetic average roughness Ra of the surface of the (c-2) component can be evaluated by the same method as the arithmetic average roughness of the surface of the (c-1) component.
[0092] In one embodiment, as a preferred example, the following examples can be cited: the arithmetic mean roughness Ra of the surface of the (c-1) component is less than 10.0 nm (preferably less than 8.0 nm, less than 3.5 nm, greater than 1.0 nm and less than 10.0 nm, greater than 1.0 nm and less than 8.0 nm, greater than 1.0 nm and less than 3.5 nm, etc.), and when the (c-2) component contains flaky conductive particles, the arithmetic mean roughness Ra of the surface of the flaky conductive particles exceeds 10.0 nm (preferably greater than 10.0 nm and less than 20 μm, etc.).
[0093] In another embodiment, as a preferred example, the following examples can be cited: the arithmetic mean roughness Ra of the surface of the (c-1) component is less than 10.0 nm (preferably less than 8.0 nm, less than 3.5 nm, greater than 1.0 nm and less than 10.0 nm, greater than 1.0 nm and less than 8.0 nm, greater than 1.0 nm and less than 3.5 nm, etc.), and the (c-2) component is a thin flake-like conductive particle having a surface arithmetic mean roughness Ra exceeding 10.0 nm (preferably exceeding 10.0 nm and being less than 20 μm, etc.).
[0094] In another embodiment, as a preferred example, the following examples can be cited: the arithmetic mean roughness Ra of the surface of the (c-1) component is less than 10.0 nm (preferably less than 8.0 nm, less than 3.5 nm, greater than 1.0 nm and less than 10.0 nm, greater than 1.0 nm and less than 8.0 nm, greater than 1.0 nm and less than 3.5 nm, etc.), and the arithmetic mean roughness Ra of the surface of the (c-2) component exceeds 10.0 nm (preferably exceeds 10.0 nm and is less than 20 μm, etc.).
[0095] (c-2) component can be surface treated with a lubricant. (c-2) preferably contains conductive particles surface treated with a lubricant, more preferably conductive particles surface treated with a lubricant. The lubricant is not particularly limited. As a lubricant, for example, saturated fatty acids and / or unsaturated fatty acids can be used. As a lubricant, it is preferred to include at least one selected from the group consisting of saturated fatty acids and unsaturated fatty acids, preferably at least one selected from the group consisting of saturated fatty acids and unsaturated fatty acids. As a lubricant, for example, capric acid, undecanoic acid, lauric acid, tridecanoic acid, myristic acid, pentadecanoic acid, palmitic acid, heptadecanoic acid, stearic acid, linolenic acid, linoleic acid, palmitoleic acid, oleic acid, etc. can be cited. From the perspective of excellent dispersibility and storage stability, stearic acid is preferred. They can be used alone or in combination of two or more. The lubricant preferably includes at least one selected from the compounds listed above, more preferably stearic acid. As an example, the lubricant is preferably at least one selected from the compounds listed above, more preferably stearic acid.
[0096] For example, as a preferred example, in the conductive resin composition, the components (c-1) and (c-2) are conductive particles (preferably silver particles) surface-treated with stearic acid.
[0097] The component (c-2) is preferably amorphous. When the component (c-2) is amorphous, it can exhibit more excellent conductivity when combined with the component (c-1).
[0098] In one embodiment, the component (c-1) is crystalline conductive particles, and the component (c-2) is amorphous conductive particles. More preferably, the component (c-1) is crystalline silver particles, and the component (c-2) is amorphous silver particles.
[0099] From the viewpoint of excellent conductivity, the average particle size of the component (c-2) is preferably 0.1 to 30 μm, more preferably 0.5 to 20 μm, further preferably 1 to 10 μm, and particularly preferably 1.0 μm or more and less than 4.0 μm. If the average particle size of the component (c-2) is 30 μm or less, a conductive resin composition having a better conductivity of the cured product can be obtained. Here, the average particle size of the component (c-2) is the particle size (D50) at a cumulative volume ratio of 50% in the particle size distribution determined by a laser diffraction scattering method.
[0100] For example, as a preferred example, in the conductive resin composition, the average particle diameters of the component (c-1) and the component (c-2) are respectively 0.1 to 30 μm.
[0101] The specific surface area of the component (c-2) is not particularly limited. In one embodiment, the specific surface area of the component (c-2) is preferably 0.01 to 10 m 2 / g, more preferably 0.1 to 5.0 m 2 / g, more preferably 0.2 to 3.0 m 2 / g, particularly preferably 0.20m 2 / g or more and less than 0.50m 2 / g. If the specific surface area of component (c-2) is 0.01m 2 / g or more, a conductive resin composition having excellent conductivity of the cured product can be obtained. When the specific surface area of the component (c-2) is 10 m 2 In another embodiment, the specific surface area of the component (c-2) is preferably 0.01 m 2 / g or more and less than 0.50m 2 / g, more preferably 0.10m 2 / g or more and less than 0.50m 2 / g, more preferably 0.20m 2 / g or more and less than 0.50m 2 Here, the specific surface area is a value calculated by the BET method.
[0102] In one embodiment, as preferred examples, the following examples can be cited: (c-1) The specific surface area of the component is 0.50 m 2 / g or more (for example, 0.50m 2 / g or more, 0.50~7.00m 2 / g, 0.50~5.00m 2 / g, 0.50~3.00m 2 / g, 0.90~3.00m 2 / g, 1.00~3.00m 2 / g, etc.), and the specific surface area of the component (c-2) is 0.01 m2 when the component (c-2) is flaky silver particles. 2 / g or more and less than 0.50m 2 / g (for example, 0.10m 2 / g or more and less than 0.50m 2 / g, 0.20m 2 / g or more and less than 0.50m 2 / g, etc.), and when the component (c-2) is particles other than flaky silver particles, it is 0.01 to 10.00 m 2 / g (e.g. 0.01~10.00m 2 / g, 0.10~5.00m2 / g, 0.20~3.00m 2 / g, etc.).
[0103] In another embodiment, as a preferred example, the following examples can be cited: (c-1) The specific surface area of the component is 0.50 m 2 / g or more (for example, 0.50m 2 / g or more, 0.50~7.00m 2 / g, 0.50~5.00m 2 / g, 0.50~3.00m 2 / g, 0.90~3.00m 2 / g, 1.00~3.00m 2 / g, etc.), component (c-2) is flaky silver particles, and the specific surface area of component (c-2) is 0.01m 2 / g or more and less than 0.50m 2 / g (for example, 0.10m 2 / g or more and less than 0.50m 2 / g, 0.20m 2 / g or more and less than 0.50m 2 / g, etc.).
[0104] In another embodiment, as a preferred example, the following examples can be cited: (c-1) The specific surface area of the component is 0.50 m 2 / g or more (for example, 0.50m 2 / g or more, 0.50~7.00m 2 / g, 0.50~5.00m 2 / g, 0.50~3.00m 2 / g, 0.90~3.00m 2 / g, 1.00~3.00m 2 / g, etc.), and the specific surface area of component (c-2) is 0.01m 2 / g or more and less than 0.50m 2 / g (for example, 0.10m 2 / g or more and less than 0.50m 2 / g, 0.20m 2 / g or more and less than 0.50m 2 / g, etc.)
[0105] As the component (c-2), a synthetic product and / or a commercial product can be used. The commercial product of the component (c-2) is not particularly limited. As a commercial product of the component (c-2), for example, SILBEST (registered trademark) TC-770 (manufactured by Tokuri Honten Co., Ltd.) can be cited.
[0106] As the component (c-2), one type of conductive particles may be used, or two or more types of conductive particles may be used in combination.
[0107] Relative to 100 parts by mass of the total of component (A) and component (B), the content of component (c-2) is preferably 50 to 500 parts by mass, more preferably 80 to 400 parts by mass, further preferably 100 to 300 parts by mass, and most preferably 150 to 250 parts by mass. By having a content of component (c-2) of 50 parts by mass or more, a conductive resin composition having excellent conductivity can be obtained, and by having a content of component (c-2) of 500 parts by mass or less, a conductive resin composition having excellent operability can be obtained. When two or more conductive particles are used as component (c-2), the content of component (c-2) refers to their total amount.
[0108] From the viewpoint of obtaining a conductive resin composition having excellent conductivity, the mass ratio of the component (c-1) to the component (c-2) is preferably 10:90 to 90:10, more preferably 15:85 to 85:15, further preferably 20:80 to 70:30, particularly preferably 22:78 to 60:40, and most preferably 25:75 to 50:50. By setting the mass ratio of the component (c-1) to the component (c-2) to be within the above range, a conductive resin composition having excellent conductivity of a cured product such as connection resistance value and volume resistivity can be obtained.
[0109] The total content of the components (c-1) and (c-2) is preferably 35% to 95% by mass, more preferably 40% to 90% by mass, further preferably 45% to 85% by mass, particularly preferably 50% to 80% by mass, and most preferably 55% to 75% by mass, relative to the total mass (100% by mass) of the conductive resin composition. When the total content of the components (c-1) and (c-2) is 35% by mass or more relative to the total mass of the conductive resin composition, a conductive resin composition having excellent conductivity can be obtained, and when the total content of the components (c-1) and (c-2) is 95% by mass or less relative to the total mass of the conductive resin composition, a conductive resin composition having excellent workability can be obtained.
[0110] The total content of the components (c-1) and (c-2) is preferably 50 to 700 parts by mass, more preferably 80 to 600 parts by mass, further preferably 100 to 500 parts by mass, particularly preferably 150 to 400 parts by mass, and most preferably 200 to 300 parts by mass relative to 100 parts by mass of the total of the components (A) and (B). By making the total content of the components (c-1) and (c-2) 50 parts by mass or more relative to 100 parts by mass of the total of the components (A) and (B), a conductive resin composition having excellent conductivity can be obtained, and by making the total content of the components (c-1) and (c-2) 700 parts by mass or less relative to 100 parts by mass of the total of the components (A) and (B), a conductive resin composition having excellent workability can be obtained.
[0111] [(D) ingredient]
[0112] The component (D) used in the present invention is an epoxy resin curing agent. As long as the component (D) cures the epoxy resin, there is no particular limitation. From the perspective of storage stability and the balance of curability, a latent epoxy resin curing agent is preferred. As a latent epoxy resin curing agent, for example, imidazole compounds, addition-type latent epoxy resin curing agents (reaction products obtained by reacting amine compounds with epoxy compounds, isocyanate compounds or urea compounds), dicyandiamide, hydrazide compounds, boron trifluoride-amine complexes, thiol compounds, acid anhydrides, etc. can be cited. From the perspective of the balance of storage stability and curability, addition-type latent epoxy resin curing agents are preferred. They can be used alone, or two or more can be used in combination. The component (D) preferably contains at least one selected from the compounds listed above, and more preferably at least one selected from the compounds listed above.
[0113] There are no particular limitations on the addition type latent epoxy resin curing agent, and examples thereof include a reaction product obtained by reacting an amine compound with an isocyanate compound or a urea compound (urea addition type latent epoxy resin curing agent), or a reaction product of an amine compound with an epoxy compound (epoxyamine addition type latent epoxy resin curing agent), etc. From the perspective of the balance between storage stability and curability, a urea addition type latent epoxy resin curing agent is preferred, and a modified aliphatic polyamine type latent epoxy resin curing agent is further preferred. The addition type latent curing agent can be used alone, or two or more types can be used in combination. The urea addition type latent curing agent and the epoxyamine addition type latent curing agent can be used alone, or two or more types can be used in combination.
[0114] Component (D) may be a liquid or a solid. From the viewpoint of storage stability, it is preferably a solid at 25°C, and more preferably a powder. It should be noted that in this specification, "solid" refers to a state in which there is substantially no fluidity at 25°C. Specifically, "a state in which there is substantially no fluidity at 25°C" means: a viscosity of 100 g / min at 25°C using a cone-plate rotational viscometer at a shear rate of 10 s -1 The viscosity measured exceeds 1000 Pa·s; or the fluidity is extremely low or non-fluid and cannot be measured using a cone-plate rotational viscometer at a shear rate of 10 s at 25°C. -1 The state of measuring viscosity.
[0115] When the (D) component is a powder, the average particle size of the powder is not particularly limited. The average particle size of the powder is preferably in the range of 0.1 to 30 μm, more preferably in the range of 0.5 to 20 μm, and most preferably in the range of 1 to 10 μm. If the average particle size of the powder is greater than 0.1 μm, the viscosity of the conductive resin composition is less likely to increase. If the average particle size of the powder is less than 30 μm, the contact area between the (E) component and the above-mentioned (A) component increases, thereby improving the curing properties. Here, the average particle size of the (D) component is the particle size (D50) at a cumulative volume ratio of 50% in the particle size distribution obtained by a laser diffraction scattering method.
[0116] As component (D), a synthetic product and / or a commercial product can be used. The commercial product of component (D) is not particularly limited, and examples of urea addition type latent epoxy resin curing agents include Fujicure FXE-1000, FXR-1020, FXR-1030, FXB-1050, and FXR-1081 (manufactured by T&K TOKA Co., Ltd.). Examples of epoxyamine addition type latent epoxy resin curing agents include Amicure PN-23, Amicure PN-H, Amicure PN-31, Amicure PN-40, Amicure PN-50, Amicure PN-F, Amicure PN-23J, Amicure PN-31J, Amicure PN-40J, Amicure MY-24, Amicure MY-25, Amicure MY-R, and Amicure PN-R (manufactured by Ajinomoto Fine-Techno Co., Inc.) etc. These may be used alone or in combination of two or more.
[0117] The content of component (D) is preferably 1 to 100 parts by mass, more preferably 5 to 80 parts by mass, further preferably 10 to 50 parts by mass, particularly preferably 12 to 45 parts by mass, and most preferably 15 to 40 parts by mass relative to a total of 100 parts by mass of component (A) and component (B). By making the content of component (D) 1 part by mass or more relative to a total of 100 parts by mass of component (A) and component (B), a conductive resin composition having excellent curability can be obtained, and by making the content of component (D) 100 parts by mass or less relative to a total of 100 parts by mass of component (A) and component (B), a conductive resin composition having excellent storage stability can be obtained. When two or more epoxy curing agents are used as component (D), the content of component (D) refers to their total amount.
[0118] [Epoxy resin with boiling point less than 300°C]
[0119] In the conductive resin composition of the present invention, the content ratio of the epoxy resin having a boiling point of less than 300°C is preferably 1.00% by mass or less, more preferably 0.10% by mass or less, and most preferably no epoxy resin is contained in the conductive resin composition as a whole. When the epoxy resin having a boiling point of less than 300°C contained in the conductive resin composition exceeds 1% by mass, unreacted components are generated as exhaust gas during heat curing, which may contaminate other parts of the electronic component. When it is 1.00% by mass or less, there is no concern about the generation of exhaust gas during heat curing.
[0120] Examples of epoxy resins having a boiling point of less than 300° C. include reactive diluents, and specifically include 1,4-butanediol diglycidyl ether, n-butyl glycidyl ether, allyl glycidyl ether, 2-ethylhexyl glycidyl ether, styrene oxide, phenyl glycidyl ether, cresol glycidyl ether, p-sec-butylphenyl glycidyl ether, glycidyl methacrylate, tert-butylphenyl glycidyl ether, diglycidyl ether, (poly)ethylene glycol glycidyl ether, butanediol glycidyl ether, trimethylolpropane triglycidyl ether, 1,6-hexanediol diglycidyl ether, 4-tert-butylphenyl glycidyl ether, and neodecanoic acid glycidyl ether.
[0121] [Organic solvents]
[0122] The conductive resin composition of the present invention preferably contains an organic solvent at a ratio of 1.00% by mass or less relative to the conductive resin composition as a whole. When the organic solvent contained in the conductive resin composition exceeds 1.00% by mass, the storage stability may be deteriorated due to the organic solvent dissolving the (D) component, or outgassing may be generated during heat curing to contaminate other parts of the electronic component. The organic solvent is preferably 1.00% by mass or less relative to the conductive resin composition as a whole, more preferably 0.10% by mass or less, and most preferably not contained. If it is 1.00% by mass or less, there is no concern about deterioration of storage stability or outgassing during heat curing.
[0123] The organic solvent is liquid at 25° C. As described above, “liquid at 25° C.” means that the organic solvent is liquid at 25° C. using a cone-plate type rotational viscometer at a shear rate of 10 s -1 The viscosity measured is 1000 Pa·s or less. When a solvent is included in the conductive resin composition, the storage stability deteriorates and the organic solvent separates due to the dissolution of the (E) component by the organic solvent, which affects the physical properties. In this specification, "the conductive resin composition does not contain an organic solvent" means that the organic solvent is intentionally not contained as a compound of the conductive resin composition, specifically, it means that the content of the organic solvent is 1% by mass or less relative to the conductive resin composition as a whole (the total mass of the conductive resin composition). Thus, in the conductive resin composition described in this embodiment, the content of the organic solvent is 0% by mass relative to the conductive resin composition as a whole (the total mass of the conductive resin composition), or exceeds 0% by mass and is 1% by mass or less. The content of the organic solvent is preferably 0.5% by mass or less, more preferably 0.1% by mass or less, and further preferably 0.01% by mass or less (lower limit: 0% by mass) relative to the conductive resin composition as a whole (the total mass of the conductive resin composition). It is particularly preferred that the conductive resin composition does not contain an organic solvent at all, that is, the content of the organic solvent is 0% by mass relative to the conductive resin composition as a whole (the total mass of the conductive resin composition). When the content of the organic solvent is 1% by mass or less based on the entire conductive resin composition (the total mass of the conductive resin composition), deterioration of storage stability and separation will not occur.
[0124] As the organic solvent, for example, aromatic organic solvents such as toluene and xylene can be listed; aliphatic organic solvents such as n-hexane; alicyclic organic solvents such as cyclohexane, methylcyclohexane and ethylcyclohexane; ketone organic solvents such as acetone and methyl ethyl ketone; alcohol organic solvents such as methanol and ethanol; ester organic solvents such as ethyl acetate and butyl acetate; and propylene glycol ether organic solvents such as propylene glycol methyl ether, propylene glycol ethyl ether and propylene glycol tert-butyl ether. When two or more organic solvents are used in combination, their content is set to the total amount. As an example, the organic solvent sometimes contains at least one organic solvent selected from aromatic organic solvents, aliphatic organic solvents, alicyclic organic solvents, ketone organic solvents, alcohol organic solvents, ester organic solvents and propylene glycol ether organic solvents, and sometimes is at least one organic solvent selected from aromatic organic solvents, aliphatic organic solvents, alicyclic organic solvents, ketone organic solvents, alcohol organic solvents, ester organic solvents and propylene glycol ether organic solvents.
[0125] In the conductive resin composition of the present invention, the total content of the epoxy resin having a boiling point of less than 300° C. and the organic solvent is preferably 1.00 mass % or less, more preferably 0.10 mass % or less, and most preferably contains no epoxy resin or organic solvent relative to the entire conductive resin composition.
[0126] [Optional Ingredients]
[0127] In addition to the above-mentioned components, various additives may be added as optional components as long as the effects of the present invention are not impaired. Examples of the additives include silane coupling agents, plasticizers, fillers (excluding component (C)), storage stabilizers, tackifiers, metal complexes, organic or inorganic pigments, rust inhibitors, defoamers, dispersants, surfactants, viscoelasticity modifiers, and thickeners.
[0128] The conductive resin composition of the present invention may contain fillers other than component (C). Examples of fillers include glass, silica, talc, mica, ceramics, calcium carbonate, carbon powder, kaolin, dry clay minerals, dry diatomaceous earth, rubber particles, etc., and rubber particles are preferred from the viewpoint of not deteriorating conductivity.
[0129] The rubber particles mentioned in the present invention refer to particles containing a layer showing rubber elasticity. The rubber particles can be particles consisting of only one layer showing rubber elasticity, or core-shell particles as particles of a multilayer structure showing rubber elasticity. From the perspective of excellent volume resistivity, core-shell particles are preferred. In addition, rubber particles previously dispersed in epoxy resin can also be used. For example, butadiene rubber, acrylic rubber, silicone rubber, butyl rubber, olefin rubber, styrene rubber, NBR, SBR, IR, EPR, etc. can be used. They can be used alone, or two or more can be used in combination.
[0130] Core-shell particles refer to particles in which the core (nucleus) and the shell (wall) of the particles are composed of polymers of different properties. In the manufacture of the preferred powder particles used in the present invention, first, as the core part, a polymerizable monomer is polymerized to manufacture it. Examples of the polymerizable monomer include (meth)acrylate monomers such as n-propyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and n-decyl (meth)acrylate, aromatic vinyl compounds such as styrene, vinyltoluene, and α-methylstyrene, vinyl cyanide compounds such as acrylonitrile and methacrylonitrile, vinylene cyanide, 2-hydroxyethyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 2-hydroxyethyl fumarate, hydroxybutyl vinyl ether, monobutyl maleate, butoxyethyl methacrylate Etc., further can enumerate ethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, hexanediol di(meth)acrylate, hexanediol tri(meth)acrylate, oligoethylene di(meth)acrylate, oligoethylene tri(meth)acrylate etc. have crosslinking monomers of more than 2 reactive groups, aromatic divinyl monomers such as divinylbenzene, triallyl trimellitate, triallyl isocyanurate etc., they can select to use 1 or different 2 or more. Then, using the polymer particles thus obtained as core, further polymerizable monomers are polymerized, and the second polymerization of the shell formed by the polymer with a melting point above room temperature is carried out. As the polymerizable monomer used at this time, it can be selected to use from the monomers identical with the polymerizable monomers for obtaining the above-mentioned core. Preferred examples of polymerizable monomers used as the shell material include (meth)acrylates having an alkyl group with 1 to 4 carbon atoms, such as ethyl (meth)acrylate, n-butyl acrylate, methyl methacrylate, and butyl methacrylate.
[0131] The core-shell particles can be synthesized by the above method, or commercial products can be used. Commercial products of the core-shell particles are not particularly limited, and for example, PARALOIDE XL-2655 (manufactured by Kureha Chemical Industry Co., Ltd.) composed of a butadiene-alkyl methacrylate-styrene copolymer, STAPHYLOID AC-3355, STAPHYLOID AC3364, STAPHYLOID TR-2105, STAPHYLOID TR-2102, STAPHYLOID TR-2122, STAPHYLOID IM-101, STAPHYLOID IM-203, STAPHYLOID IM-301, STAPHYLOID IM-401 and STAPHYLOID IM-406 composed of an acrylate-acrylonitrile-styrene copolymer, STAPHYLOID IM-601 composed of an acrylate-acrylonitrile-styrene copolymer, Zefiac F-351G (manufactured by Aica Kogyo) composed of a polymethacrylate polymer can be used. Co., Ltd.), PARALOIDE XL-2314, EXL-2611, EXL-3387 (manufactured by Dow Chemical Japan Limited), etc. These may be used alone or in combination of two or more.
[0132] The particle size of the rubber particles is preferably 0.01 to 10 μm, particularly preferably 0.05 to 5 μm. When the particle size is 0.01 μm or more, an increase in viscosity can be suppressed, and when the particle size is 10 μm or less, a conductive resin composition having excellent conductivity can be obtained.
[0133] The content of the rubber particles is preferably 0.01 to 20 parts by mass, more preferably 0.03 to 10 parts by mass, and most preferably 0.05 to 5 parts by mass relative to 100 parts by mass of the total of the components (A) and (B). By being within the above range, a conductive resin composition having excellent conductivity such as connection resistance value and volume resistivity can be obtained.
[0134] As the rubber particles dispersed in the epoxy resin in advance, specifically, there can be mentioned rubber particles dispersed in the epoxy resin by a mixing and stirring device such as a high-power homogenizer, and rubber particles synthesized by emulsion polymerization in the epoxy resin. These can be used alone or in combination of two or more. The epoxy resin in which the rubber particles are dispersed is treated as the above-mentioned component (A) or component (B).
[0135] Commercially available products of rubber-dispersed epoxy resins include KaneAce MX-153, MX-136, MX-257, MX-127, and MX-451 (manufactured by KANEKA CORPORATION), ACRYSET BPF-307, and BPA-328 (manufactured by Nippon Shokubai Co., Ltd.), etc. These may be used alone or in combination of two or more.
[0136] The conductive resin composition of the present invention may contain a storage stabilizer. As a storage stabilizer, there is no particular limitation as long as the storage stability is improved, and borate compounds, phosphoric acid, alkyl phosphates, p-toluenesulfonic acid, methyl p-toluenesulfonate, etc. may be used. As borate compounds, for example, trimethyl borate, triethyl borate, tri-n-propyl borate, triisopropyl borate, tributyl borate, trihexyl borate, tri-n-octyl borate, tri(2-ethylhexyloxy)borane, triphenyl borate, trimethoxyboroxine, 1,3,2-dioxaborolane-4,5-dione, etc. may be cited. In addition, as a commercial product of a borate compound, for example, "CUREDUCT L-07N" (manufactured by Shikoku Chemical Industry Co., Ltd.) may be cited. As alkyl phosphates, trimethyl phosphate, tributyl phosphate, etc. may be used, but are not limited to these. The storage stabilizer may be used alone or in combination. In consideration of storage stability, phosphoric acid, tributyl borate, trimethoxyboroxine, methyl p-toluenesulfonate, and 1,3,2-dioxaborolane-4,5-dione are preferred.
[0137] The conductive resin composition of the present invention may contain a metal complex. Although the exact reason is not known, the addition of the metal complex improves the conductivity of the adherend whose outermost surface is nickel. Examples of the metal contained in the metal complex include zinc, aluminum, iron, cobalt, nickel, tin, copper, etc., and examples of the organic ligand include acetate, acetoacetate, hexanoate, phthalocyanate, etc., but are not limited to these.
[0138] Examples of the metal complex include copper oleate (divalent), zinc acetoacetate (divalent), aluminum acetoacetate (divalent), cobalt acetoacetate (divalent), nickel acetate, nickel acetoacetate (divalent), iron phthalocyanine (divalent), dibutyltin dilaurate, etc., but are not limited to these.
[0139] Specific examples of the metal complex include NACEM Zn, NACEM AL, NACEM Co, and NACEM Ni as acetylacetone metal complex series manufactured by Nippon Chemical Industry Co., Ltd., and KS-1260 manufactured by Kyodo Chemical Co., Ltd. as octanoate metal soap series, but are not limited thereto.
[0140] The conductive resin composition of the present invention preferably contains 0.01 to 20 parts by mass of the metal complex, more preferably 0.5 to 15 parts by mass, relative to 100 parts by mass of the total of the components (A) and (B). When the metal complex is contained in an amount of 0.01 parts by mass or more, the connection resistance is reduced, and when the metal complex is contained in an amount of 20 parts by mass or less, the storage stability can be maintained.
[0141] The conductive resin composition described in one embodiment is substantially composed of the above-mentioned (A) to (D) components and at least one selected from the group consisting of a storage stabilizer, a silane coupling agent, a filler (preferably rubber particles) and a metal complex. The conductive resin composition described in a preferred embodiment is substantially composed of the above-mentioned (A) to (D) components and a storage stabilizer. In the above embodiment, "the conductive resin composition is substantially composed of X" means that when the total mass of the conductive resin composition is set to 100 mass% (relative to the entire conductive resin composition), the total content of X exceeds 99 mass% (upper limit: 100 mass%). For example, “the conductive resin composition of the present invention consists essentially of the above-mentioned components (A) to (D) and at least one selected from the group consisting of a storage stabilizer, a silane coupling agent, a filler (preferably rubber particles) and a metal complex” means that the total content (total addition amount) of the above-mentioned components (A) to (D), the storage stabilizer, the silane coupling agent, the filler (preferably rubber particles) and the metal complex exceeds 99% by mass (upper limit: 100% by mass) when the total mass of the conductive resin composition is 100% by mass (relative to the entire conductive resin composition). For example, “the conductive resin composition of the present invention consists essentially of the above-mentioned components (A) to (D) and a storage stabilizer” means that the total content (total addition amount) of the above-mentioned components (A) to (D) and the storage stabilizer exceeds 99% by mass (upper limit: 100% by mass) when the total mass of the conductive resin composition is 100% by mass (relative to the entire conductive resin composition).
[0142] The conductive resin composition described in this embodiment generates less gas. For example, in the gas exhaust test of the embodiment described later, the mass reduction when the conductive resin composition is heated is less than 0.2 mass%. Specifically, the mass reduction of the conductive resin composition described in the above embodiment is preferably less than 0.2 mass%, more preferably less than 0.20 mass%, more preferably less than 0.15 mass% or less, and particularly preferably less than 0.15 mass%. In addition, the mass reduction of the conductive resin composition described in the above embodiment is preferably less than 0.2 mass%, more preferably less than 0.20 mass%, more preferably less than 0.15 mass% or less, and particularly preferably less than 0.15 mass%. In addition, the mass reduction of the conductive resin composition described in the above embodiment is preferably less than 0.2 mass%, more preferably less than 0.20 mass%, more preferably less than 0.15 mass% or less, and particularly preferably less than 0.15 mass%.
[0143] <Cured product>
[0144] The conductive resin composition described in the above embodiment can be cured by heating, and can be cured even at low temperatures (lower than 100° C.). Therefore, another embodiment of the present invention relates to a cured product obtained by curing the conductive resin composition described in the above embodiment (cured product of the conductive resin composition).
[0145] The conductive resin composition of the present invention can be cured at low temperature (less than 100°C). In the heating conditions of the curing method of the conductive resin composition of the present invention, the heating curing temperature is not particularly limited. For example, from the viewpoint of less damage to the components of the adherend, it is preferably a temperature of 45°C to 100°C, and more preferably 50°C to 95°C. The heating curing time is not particularly limited. In the case of a heating curing temperature of 45°C to 100°C, from the viewpoint of production efficiency of the manufacturing method using the conductive resin composition of the present invention, it is preferably 10 minutes to 3 hours, and more preferably 30 minutes to 2 hours. The cured product obtained by curing the conductive resin composition of the present invention is also part of the embodiment of the present invention.
[0146] The method for manufacturing the cured product (the curing method of the conductive resin composition) is not particularly limited, and a known method can be used. As an example, a method in which the conductive resin composition described in the above manner is applied to the adherend and then heated to cure it can be cited. Therefore, in order to make the operability during coating good, the conductive resin composition is preferably a liquid (liquid). As an example, the viscosity of the conductive resin composition at 25°C is preferably 0.01Pa·s or more and less than 100Pa·s, more preferably 0.1~50Pa·s, further preferably 0.5~50Pa·s, particularly preferably 1~20Pa·s, and further particularly preferably 1~10Pa·s.
[0147] When applying the conductive resin composition, the thickness of the coating film is not particularly limited and can be appropriately adjusted within the range that can bond the adherend. In addition, the heating conditions (curing conditions) are not particularly limited as long as they are conditions that can fully cure the conductive resin composition. In the heating conditions of the curing method of the conductive resin composition, the heating curing temperature is not particularly limited. For example, from the viewpoint of reducing the effect of heat on the adherend, a temperature of 45°C to 100°C is preferred, and a temperature of 50°C to 95°C is more preferred. The heating curing time is not particularly limited. In the case of a heating curing temperature of 45°C to 100°C, from the viewpoint of reducing the effect of heat on the adherend, it is preferably 10 minutes to 3 hours, and more preferably 30 minutes to 2 hours.
[0148] <Adhesive>
[0149] The conductive resin composition of the present invention can be used for electronic components that require conductivity, etc., and from the aspect of excellent conductivity and adhesion, it can be used for adherends with poor conductivity as the most surface nickel. That is, the conductive resin composition described in one embodiment of the present invention and the cured product described in another embodiment of the present invention are preferably used for adherends with nickel as the most surface. Here, as the adherend with nickel as the most surface, there is no particular restriction, mainly the adherend with nickel plating, for example, components (wires, printed circuit (base) boards, etc.) after electrolytic plating or non-electrolytic plating can be cited to SPCC (cold-rolled steel sheet), stainless steel, and copper components. For the conductive resin composition with the above-mentioned structure, although it is not known to have a clear reason, even if it is an adherend with nickel as the most surface, the connection resistance value of the cured product can be reduced, and the storage stability is excellent, and then the excellent disposability can be exerted.
[0150] <Other Implementation Methods>
[0151] The conductive resin composition of the present invention can also be used appropriately when moderate conductivity is required. At this time, according to another embodiment of the present invention, the following conductive resin composition can also be provided, which contains the following (B) to (D) components:
[0152] (B) component: a glycidylamine type epoxy resin having a boiling point of 300° C. or higher;
[0153] (C) component: conductive particles;
[0154] (D) Component: epoxy resin curing agent.
[0155] The conductive resin composition according to this embodiment has a conductivity of 10Ω or less as measured by the method of Examples described below, for example. The conductive resin composition according to this embodiment reduces the generation of outgassing and has excellent conductivity and adhesiveness.
[0156] Example
[0157] Next, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples. Unless otherwise specified, the test was carried out under an environment of 25° C. and 55% RH.
[0158] [Examples 1 to 10, Comparative Examples 1 to 3, Reference Examples 1 to 3]
[0159] In order to prepare the conductive resin composition, the following components are prepared. Hereinafter, the conductive resin composition is also simply referred to as a composition.
[0160] (A) Ingredient: Bisphenol epoxy resin
[0161] · EPICLON EXA-835LV (boiling point 470°C or higher (mixture of bisphenol A epoxy resin (boiling point: 487°C) and bisphenol F epoxy resin (boiling point: 474°C), mixing mass ratio 50:50), epoxy equivalent: 165 g / eq, viscosity (25°C): 2000 mPa·s (2 Pa·s), manufactured by DIC Corporation)
[0162] Component (B): Epoxy resin with a boiling point of 300°C or higher (excluding component (A))
[0163] · ADEKA RESIN EP-3950S (N,N-diglycidyl-4-glycidyloxyaniline, trifunctional glycidylamine type epoxy resin, boiling point: 420°C, epoxy equivalent: 95 g / eq, viscosity (25°C): 650 mPa·s (0.65 Pa·s), manufactured by ADEKA CORPORATION)
[0164] (B') Component: Epoxy resin with a boiling point of less than 300°C
[0165] ·CARDURAE 10P (neodecanoic acid glycidyl ester, reactive diluent, boiling point: 278°C, manufactured by Momentive Performance Materials Inc.)
[0166] ・ADEKA GLYCIROL ED-509S (4-tert-butylphenyl glycidyl ether, reactive diluent, boiling point: 294°C, manufactured by ADEKA CORPORATION)
[0167] (C) Component: Conductive particles
[0168] (c-1): Plate-shaped conductive particles
[0169] M27 (single crystal, silver particles, plate-shaped, stearic acid surface treatment, average particle size (D50): 4.5 μm, average thickness (T): 80 nm, aspect ratio (D50 / T): 56, specific surface area: 1.0 m 2 / g, TOKUSEN KOGYO Co., Ltd.)
[0170] LM1 (single crystal, silver particles, plate-shaped, stearic acid surface treatment, average particle size (D50): 1.0 μm, average thickness (T): 60 nm, aspect ratio (D50 / T): 1.6, specific surface area: 1.0 m 2 / g, TOKUSEN KOGYO Co., Ltd.)
[0171] N300 (single crystal, silver particles, plate-shaped, stearic acid surface treatment, average particle size (D50): 0.4 μm, average thickness (T): 50 nm, aspect ratio (D50 / T): 8, specific surface area: 2.4 m 2 / g, TOKUSEN KOGYO Co., Ltd.)
[0172] (c-2): Conductive particles other than (c-1)
[0173] · SILBEST TC-770 (Flake silver particles (silver particles: amorphous), stearic acid surface treatment, average particle size (D50): 3.5 μm, specific surface area: 0.45 m 2 / g, Made by Tokuli Co., Ltd.)
[0174] (D) Component: Epoxy resin curing agent
[0175] FUJICURE FXR-1081 (modified aliphatic polyamine latent curing agent (urea addition type latent curing agent), average particle size (D50): 5 μm, manufactured by T&K TOKA Co., Ltd.)
[0176] Any ingredient
[0177] CUREDUCT L-07N (storage stabilizer, epoxy-phenol-borate complex (containing bifunctional bisphenol A type epoxy resin: 91 mass %, phenol novolac resin: 4 mass %, 2,2'-(carbonyldioxy)bis(1,3,2-dioxaborolane-4,5-dione: 5 mass %), manufactured by Shikoku Chemical Industry Co., Ltd.).
[0178] It should be noted that the above-mentioned SILBEST (registered trademark) TC-770 (manufactured by Tokurei Honten Co., Ltd.) used as (c-2) has a flaky shape. However, the thickness of SILBEST (registered trademark) TC-770 (manufactured by Tokurei Honten Co., Ltd.) varies greatly within one particle, the upper and lower surfaces of the flaky shape are obviously not parallel, and significant concavities and / or significant height differences are confirmed on the surface of the particle. Therefore, SILBEST (registered trademark) TC-770 (manufactured by Tokurei Honten Co., Ltd.) is not a plate-shaped silver particle, but a flaky silver particle.
[0179] The method for manufacturing the composition described in Examples 1 to 12, Comparative Examples 1 to 3, and Reference Example 1 is as follows. Weigh component (A), component (B) (or component (B')), component (C) and any component, and stir for 30 minutes using a planetary mixer. Next, weigh component (D) and add it, and use a planetary mixer to perform vacuum degassing for 30 minutes while stirring to obtain a conductive resin composition. The conductive resin composition obtained is in liquid form at 25°C. The detailed preparation amounts are shown in Tables 1 and 2, and all values are expressed in parts by mass.
[0180] <Exhaust test>
[0181] 20 mg of each composition was weighed, and each composition in an uncured state was heated from 25°C to 80°C at a heating temperature of 10°C / min using a thermal weight loss measuring device TG / DTA220 manufactured by Seiko Instruments, and then continuously measured at 80°C for 2 hours, and the mass reduction after 1 hour and 2 hours was measured. The mass reduction measured formally was regarded as the amount of exhaust gas generated. If the mass reduction is preferably less than 0.2% by mass, and more preferably less than 0.20% by mass, it is preferred that the electronic components will not be contaminated.
[0182] <Conductivity Test>
[0183] On a masking tape with a width of 10 mm and a thickness of 100 μm, 5 holes with a diameter of 5 mm × 5 holes are opened at intervals of 10 mm along the length direction. The masking tape is attached to an electroless nickel-plated plate with a width of 25 mm × a length of 100 mm × a thickness of 1.6 mm, and the composition is scraped. When scraping, be careful not to mix bubbles into the composition. Next, the masking tape is peeled off and heated to 80°C × 1 hour in a hot air drying furnace to cure the composition. After the temperature of the test piece drops to room temperature, the needle-shaped electrode of the dual-display multimeter is brought into contact with the cured product of the adjacent composition to measure the resistance. Thus, the resistance value (volume resistivity) of the resin itself and the resistance (connection resistance value) generated between the conductive resin composition and the electroless nickel-plated plate are measured, and the total value is taken as "conductivity (Ω)". If the conductivity is less than 5.00Ω, it is practically allowed, preferably less than 1.00Ω, more preferably less than 0.50Ω, and most preferably less than 0.30Ω (lower limit 0Ω).
[0184] <Die Adhesion Strength Measurement>
[0185] A masking tape was attached to an electroless nickel-plated plate having a thickness of 1.6 mm, a width of 25 mm, and a length of 100 mm so as to have a width of 5 mm and a thickness of 50 μm. The composition was then scraped to form a uniform coating film, and then the masking tape was peeled off. A ceramic chip is dropped vertically onto the coating from 1 cm above the coating to prepare a test piece (n=5). The test piece is heated to 80°C for 1 hour in a hot air drying furnace to cure the composition. After the temperature of the test piece drops to room temperature, the digital dynamometer with contacts is moved at 50 mm / min while the nickel-plated plate is fixed. The chip is pushed by the contacts in a direction perpendicular to the long side of the test piece to measure the "maximum strength (N)". The "chip bonding force (MPa)" is calculated by converting the bonding area. In order to prevent the adherend from falling off, it is preferably 10 MPa or more, more preferably 15 MPa or more, and most preferably 20 MPa or more. In addition, "-" in the table means not measured.
[0186] [Table 1]
[0187]
[0188] [Table 2]
[0189]
[0190] Examples 1 to 5, Example 11, and Example 12 are compositions containing components (A) to (D) and having different mass ratios of component (A) to component (B), and it was confirmed that: the conductivity and adhesion are excellent, and the mass reduction in the exhaust test is also suppressed to a low level. In addition, Example 6 is a composition with a high content of component (C), and it is known that: the conductivity is excellent. Furthermore, Example 7 and Example 8 are compositions formed by combining plate-like conductive particles (c-1) with different particle sizes, and both confirmed that: the conductivity and adhesion are excellent, and the mass reduction in the exhaust test is also suppressed to a low level. Example 9 and Example 10 are compositions containing (c-1) or (c-2) alone, and both confirmed that: the conductivity and adhesion are excellent, and the mass reduction in the exhaust test is also suppressed to a low level.
[0191] On the other hand, Comparative Example 1 is a composition not containing component (B), and it was confirmed that in the exhaust test, the mass reduction was large and the amount of exhaust gas generated was large. In addition, Comparative Examples 2 and 3 are compositions containing a low-boiling-point epoxy resin as component (B') instead of component (B), and it was confirmed that although the conductivity was excellent, in the exhaust test, the mass reduction was large and the amount of exhaust gas generated was large.
[0192] In addition, Reference Example 1 is a composition not containing the component (A), and it was confirmed that the mass reduction was also suppressed to a low level in the exhaust gas test.
[0193] Industrial Applicability
[0194] The conductive resin composition of the present invention has excellent conductivity and can suppress the amount of outgassing, so it is useful in the conduction / bonding applications for electrical / electronic components, and can especially reduce the resistance value for metals such as nickel whose conductivity is easily deteriorated. In addition, by suppressing the generation of outgassing, it can be suitably used for electronic components around lenses where contamination is a concern.
[0195] This application is based on Japanese Patent Application No. 2022-105366 filed on June 30, 2022, the disclosure of which is referenced and cited in the present specification in its entirety.
Claims
1. A conductive resin composition comprising the following components (A) to (D): (A) ingredient: bisphenol epoxy resin; (B) component: an epoxy resin having a boiling point of 300°C or higher, which does not include (A) component; (C) component: conductive particles; (D) Component: epoxy resin curing agent.
2. The conductive resin composition according to claim 1, wherein The content of the epoxy resin having a boiling point lower than 300° C. and the solvent is 1.00% by mass or less based on the total mass of the composition.
3. The conductive resin composition according to claim 1 or 2, wherein The component (B) is an epoxy resin having a boiling point of 300° C. or higher and containing two or more epoxy groups.
4. The conductive resin composition according to claim 1 or 2, wherein The component (B) is a glycidylamine type epoxy resin.
5. The conductive resin composition according to claim 1 or 2, wherein The mass ratio of the component (A) to the component (B) is 99:1 to 60:40 expressed as (component (A):component (B).
6. The conductive resin composition according to claim 1 or 2, wherein The component (C) includes plate-like conductive particles as the component (c-1) and conductive particles other than the component (c-1) as the component (c-2).
7. The conductive resin composition according to claim 6, wherein The components (c-1) and (c-2) are silver particles.
8. The conductive resin composition according to claim 7, wherein The mass ratio of the component (c-1) to the component (c-2) is 20:80 to 70:30 expressed as component (c-1):component (c-2).
9. The conductive resin composition according to claim 1 or 2, wherein The component (D) is a latent epoxy resin curing agent.
10. The conductive resin composition according to claim 1 or 2, wherein The component (D) is a modified aliphatic polyamine latent epoxy resin curing agent.
11. The conductive resin composition according to claim 1 or 2, wherein The uncured conductive resin composition was heated from 25° C. to 80° C. at a heating rate of 10° C. / min and then heated at 80° C. for 1 hour. The mass loss at this time was less than 0.2 mass %. 12 . A cured product obtained by curing the conductive resin composition according to claim 1 or 2.
13. A conductive resin composition comprising the following components (B) to (D): (B) component: a glycidylamine type epoxy resin having a boiling point of 300° C. or higher; (C) component: conductive particles; (D) Component: epoxy resin curing agent.
Citation Information
Patent Citations
Fine flaky particles
JP2014196527A
Conductive adhesive
JP2020139020A
Non-permanent site cooling system and non-permanent site cooling method
JP2022105366A
Flake-like fine particles
US20160001362A1